Energy harvesting using the FER–FEO phase transformation in [011] cut single crystal PIN-PMN-PT. (September 2014) - Dong, Wen D; Finkel, Peter; Amin, Ahmed; Cunefare, Kenneth A; Lynch, Christopher S
This study addresses the effects of frequency and load resistance on energy harvesting using a mechanically excited ferroelectric rhombohedral to ferroelectric orthorhombic phase transformation in [011] cut Pb(In1/2 Nb1/2 )O3 –Pb(Mg1/3 Nb2/3 )O3 –PbTiO3 (PIN-PMN-PT) single crystals. The crystals were mechanically driven through the phase transformation, and voltage across a resistive load was measured. The effects of frequency and resistive load on the electrical energy generated were measured. Over the range of frequencies and load impedances tested, the crystals behaved as a charge source. The current increased linearly with frequency, and the voltage increased linearly with load impedance. Impedance matching to maximize the energy harvested is discussed. The energy harvested using the phase transformation was on average 27 times, with a peak of 108 times, the energy harvested using the same crystals operating in the linear piezoelectric regime under the same stress excitation amplitude.